A pharmacophore‐based classification better predicts the outcomes of HER2‐negative breast cancer patients receiving the anthracycline‐ and/or taxane‐based neoadjuvant chemotherapy. (2nd June 2021) - Li, Xuan; Sun, Hefen; Liu, Qiqi; Liu, Yang; Hou, Yifeng; Jin, Wei
Abstract: Aims: Prognosis of patients for human epidermal growth factor receptor 2 (HER2)‐negative breast cancer post neoadjuvant chemotherapy is not well understood. The aim of this study was to develop a novel pharmacophore‐based signature to better classify and predict the risk of HER2‐negative patients after anthracycline‐and/or taxane‐based neoadjuvant chemotherapy (NACT). Main methods: Anthracycline and taxane pharmacophore‐based genes were obtained from PharmMapper. Drug‐targeted genes (DTG) related clinical and bioinformatic analyses were undertaken in four GEO datasets. Key findings: We used 12 genes from the pharmacophore to develop a DTG score (DTG‐S). The DTG‐S classification exhibited significant prognostic ability with respect to disease free survival (DFS) for HER2‐negative patients who receive at least one type of neoadjuvant chemotherapy that included anthracycline and/or taxane. DTG‐S associated with a high predictive ability for pathological complete response (pCR) as well as for prognosis of breast cancer. Using the DTG‐S classification in other prediction models may improve the reclassification accuracy for DFS. Combining the DTG‐S with other clinicopathological factors may further improve its predictive ability of patients' outcomes. Gene ontology and KEGG pathway analysis showed that the biological processes of DTG‐S high group were associated with the cell cycle, cell migration, and cell signal transduction pathways. Targeted drug analysis shows that some CDK inhibitors and PI3K‐AKT pathway inhibitors may be useful for high DTG‐S patients. Significance: The DTG‐S classification adds prognostic and predictive information to classical parameters for HER2‐negative patients who receive anthracycline‐and/or taxane‐based NACT, which could improve the patients' risk stratification and may help guide adjuvant treatment. Abstract : Our pharmacophore‐based 12‐gene drug‐targeted genes score (DTG‐S) displays better predictive values for DFS and for pathological response to anthracycline‐and/or taxane‐based chemotherapy in human epidermal growth factor receptor 2 negative breast cancer. The biological relevance of the signature were cell cycle and cell signal transduction. The targeted drug analysis shows that some CDK inhibitors which can block the cell cycle and PI3K‐AKT pathway inhibitors may useful for high DTG‐S patients.